A Systematic Review of Animal Models of NAFLD Finds High‐Fat, High‐Fructose Diets Most Closely Resemble Human NAFLD. Issue 4 (17th June 2021) - Im, Yu Ri; Hunter, Harriet; de Gracia Hahn, Dana; Duret, Amedine; Cheah, Qinrong; Dong, Jiawen; Fairey, Madison; Hjalmarsson, Clarissa; Li, Alice; Lim, Hong Kai; McKeown, Lorcán; Mitrofan, Claudia‐Gabriela; et al.
Abstract : Background and Aims: Animal models of human disease are a key component of translational hepatology research, yet there is no consensus on which model is optimal for NAFLD. Approach and Results: We generated a database of 3, 920 rodent models of NAFLD. Study designs were highly heterogeneous, and therefore, few models had been cited more than once. Analysis of genetic models supported the current evidence for the role of adipose dysfunction and suggested a role for innate immunity in the progression of NAFLD. We identified that high‐fat, high‐fructose diets most closely recapitulate the human phenotype of NAFLD. There was substantial variability in the nomenclature of animal models: a consensus on terminology of specialist diets is needed. More broadly, this analysis demonstrates the variability in preclinical study design, which has wider implications for the reproducibility of in vivo experiments both in the field of hepatology and beyond. Conclusions: This systematic analysis provides a framework for phenotypic assessment of NAFLD models and highlights the need for increased standardization and replication.